Analysis of the Relationship of Concrete Column Structural Elements to Steel Frame Beams Supporting Swimming Pool Loads in the East Coast Center II Phase 2 Surabaya Project - Sumaidi; Wahyu Kartini; Rida Pribady (Future Science, 2024)
The swimming pool is located on the top floor of the building with a large swimming pool making structural design pay attention to all aspects, especially safety aspects when used. The structural method used in this study is a combination of structures between concrete columns and Bailey model steel frame beams. The use of steel frame beams is because the swimming pool has an area of 27 m x 20,5 m and under the swimming pool there should be no columns to create a spacious room. In the combination of these structures, the relationship between concrete columns and steel frame beams (JCB) is connected using anchors as a component that transfers loads. The anchor used is an L-shaped anchor model. The anchor is connected at four end points of the steel frame beam which helps transfer the load to the concrete column. From the results of the analysis with ETABS software, the largest value of the axial force (Fz) is 5525113,22 N and the shear force (Fx) is 6438725 N. According to SNI 2847: 2019, the anchor needed to reduce the axial force and shear force is used 52 36 mm diameter anchors with a shear capacity value of 6496089,6 N and an axial capacity value of 12492480 N.